2010
DOI: 10.1038/sj.bjc.6605925
|View full text |Cite
|
Sign up to set email alerts
|

Identification of serum angiopoietin-2 as a biomarker for clinical outcome of colorectal cancer patients treated with bevacizumab-containing therapy

Abstract: Background:The combination of chemotherapy with the vascular endothelial growth factor (VEGF) antibody bevacizumab is a standard of care in advanced colorectal cancer (CRC). However, biomarkers predicting outcome of bevacizumab-containing treatment are lacking. As angiopoietin-2 (Ang-2) is a key regulator of vascular remodelling in concert with VEGF, we investigated its role as a biomarker in metastatic CRC.Methods:Serum Ang-2 levels were measured in 33 healthy volunteers and 90 patients with CRC. Of these, 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
122
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(141 citation statements)
references
References 32 publications
(42 reference statements)
15
122
1
Order By: Relevance
“…In contrast to these findings, other studies have shown a correlation between high levels of circulating Ang-2 and a poorer prognosis in melanoma patients 34 and in patients with advanced colorectal cancer treated with bevacizumab. 35 Although baseline-circulating Ang-2 was not prognostic for outcome in our mRCC patients, a decrease in circulating Ang-2 appeared to be predictive for sunitinib-induced reduction in total tumor burden.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In contrast to these findings, other studies have shown a correlation between high levels of circulating Ang-2 and a poorer prognosis in melanoma patients 34 and in patients with advanced colorectal cancer treated with bevacizumab. 35 Although baseline-circulating Ang-2 was not prognostic for outcome in our mRCC patients, a decrease in circulating Ang-2 appeared to be predictive for sunitinib-induced reduction in total tumor burden.…”
Section: Discussionmentioning
confidence: 55%
“…As conflicting data have been published on tissue localization of Ang-2 expression in malignancies, 30,35 we further explored whether the changes in circulating Ang-2 were possibly of endothelial origin. Hence, HUVECS were treated with sunitinib to determine changes in Ang-2 in supernatant.…”
Section: Discussionmentioning
confidence: 99%
“…However, several in situ hybridization studies have revealed increased levels of Ang2 expression in cancers of different origin, including neuroendocrine tumors (Detjen et al 2010), hepatocellular cancer (Chen et al 2001;Scholz et al 2007), gastric cancer (Moon et al 2006), angiosarcoma (Brown et al 2000), carcinosarcoma (Emoto et al 2004), and astrocytoma (Zagzag et al 1999). Interestingly, some studies report increased expression of Ang2 in both endothelial cells and tumor cells (e.g., Helfrich et al 2009;Detjen et al 2010), whereas other studies have shown Ang2 expression limited to the vasculature and not in tumor cells (Stratmann et al 1998;Zagzag et al 1999;Moon et al 2006;Goede et al 2010). In addition to in situ hybridization methods, analyses of RNA from whole and microdissected tissue have shown increased Ang2 in tumors versus corresponding normal tissue (e.g., Durkin et al 2004;Helfrich et al 2009;Goede et al 2010).…”
Section: Expression Of Ang2 Is Increased In Several Disease Settingsmentioning
confidence: 99%
“…Interestingly, some studies report increased expression of Ang2 in both endothelial cells and tumor cells (e.g., Helfrich et al 2009;Detjen et al 2010), whereas other studies have shown Ang2 expression limited to the vasculature and not in tumor cells (Stratmann et al 1998;Zagzag et al 1999;Moon et al 2006;Goede et al 2010). In addition to in situ hybridization methods, analyses of RNA from whole and microdissected tissue have shown increased Ang2 in tumors versus corresponding normal tissue (e.g., Durkin et al 2004;Helfrich et al 2009;Goede et al 2010).…”
Section: Expression Of Ang2 Is Increased In Several Disease Settingsmentioning
confidence: 99%
“…Circulating VEGF-A, or short VEGF-A isoforms did not correlate with PFS/ OS outcomes (67,68). Preclinical work has suggested that alternative members of the VEGF signaling family [Placental growth factor (PlGF), VEGF-C and VEGF-D] can stimulate angiogenesis in the setting of VEGF-A blockade with bevacizumab (69,70).…”
Section: Alternative Isoforms Of Vegfmentioning
confidence: 99%